EFFECT OF MACROECONOMY, CAPITAL ADEQUACY RATIO, AND NON PERFORMING FINANCING ON RETURN ON ASSETS : Study Empirical at PT. Bank Syariah Mandiri - Muhammad Nasir Nasir; Muhammad Yazid AR; Rusydi Rusydi Rusydi; Anggya Sophia Imannisa (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
The purpose of this study is to determine the influence of macroeconomic, CAR, and NPF variables against ROA at PT. Bank Syariah Mandiri in Indonesia. The data used in this study was Time Series data from 2008-2019. The sample in this study uses the saturated or census sampling method, where the entire population is sampled.The research method used in this study is a multiple regression with the smallest quadratic equation. The results showed that simultaneously inflation, GDP, price of gold, CAR and NPF had significant effect on ROA. In partial GDP, and NPF have negative and significant effect on ROA, while inflation, gold prices, and CAR have no significant effect on ROA. The fifth ability of the variable explains ROA by 67.6% while the remaining 32.4% is influenced or explained by other variables not included in the study. These results are expected to be beneficial to sharia banking, especially PT Bank Syariah Mandiri Syariah in order to better improve the future performance